The Implementation of Character Education in the Independent Curriculum in Elementary Schools - Maulana, Aan; Haifaturrahman, Haifaturrahman; Muhdar, Syafruddin (STIT Ahlussunnah Bukittinggi, 2025)
Character education plays an important role in shaping students' personalities, including moral, ethical, and social values. The Merdeka Curriculum, which has been implemented since 2022, provides opportunities for the integration of character education into learning in elementary schools. This study aims to evaluate the implementation of character education in the Merdeka Curriculum, as well as the challenges faced by teachers in implementing character values in daily learning. This study uses a qualitative approach with interviews and observations of teachers in several elementary schools. The results show that integrated character education can improve students' positive attitudes and behavior, but the biggest challenge is the lack of teacher skills in implementing character consistently. Therefore, this study recommends the need for more intensive teacher training to integrate character education into every aspect of learning.